2022
DOI: 10.21037/tcr-21-2853
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and immunological significance of peroxisome proliferator-activated receptor gamma in hepatocellular carcinoma based on multiple databases

Abstract: Background: Peroxisome proliferator-activated receptor gamma (PPARG) plays some roles in preventing liver disease progression to hepatocellular carcinoma. However, there is limited information about the function of PPARG of in hepatocellular carcinoma. This study aimed to determine the significance of PPARG in immunological response and as a biomarker for hepatocellular carcinoma survival.Methods: We investigated the expression, prognosis, Kyoto Encyclopedia of Genes and Genomes/ Gene Ontology biological proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Furthermore, dyslipidemia often accompanies obesity and can result in the accumulation of lipids in hepatocytes, which can progress to MASH, liver cirrhosis, and eventually HCC. Peroxisome proliferator-activated receptor gamma (PPAR-γ) and sterol regulatory element-binding protein-1c (SREBP-1c) are key transcription factors that regulate lipid metabolism and are implicated in the link between obesity and HCC [155]. Activation of these pathways leads to increased lipid synthesis and storage, contributing to liver carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dyslipidemia often accompanies obesity and can result in the accumulation of lipids in hepatocytes, which can progress to MASH, liver cirrhosis, and eventually HCC. Peroxisome proliferator-activated receptor gamma (PPAR-γ) and sterol regulatory element-binding protein-1c (SREBP-1c) are key transcription factors that regulate lipid metabolism and are implicated in the link between obesity and HCC [155]. Activation of these pathways leads to increased lipid synthesis and storage, contributing to liver carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that in the HCC cohort, the simultaneous high expressions of USP22/PPARγ/ACACA were associated with poor OS 64 . Through bioinformatics analysis and experimental validation, Wang et al 82 . have discovered that there is a positive correlation between PPARγ and TP53 mutation in HCC, and the high expression of PPARγ indicates a poor prognosis.…”
Section: Ppars and Related Pathways As Prognostic Biomarkersmentioning
confidence: 99%
“… 64 Through bioinformatics analysis and experimental validation, Wang et al. 82 have discovered that there is a positive correlation between PPARγ and TP53 mutation in HCC, and the high expression of PPARγ indicates a poor prognosis. Immunohistochemistry was used to detect the expression of PPARγ in 83 HCC tissues, and the relationship between the PPARγ expression and clinical pathology was analysed.…”
Section: Ppars and Related Pathways As Prognostic Biomarkersmentioning
confidence: 99%